Analysis of Factors Related to Low Back Pain in Stone Cutting Workers in Pero Village, Southwest Sumba District - Robertus Ngongo Lelu; Utma Aspatria; Amelya B. Sir (Universitas Nusa Cendana, 2022)
Low back pain is a health problem often experienced by stone-cutting workers. This study aims to analyze the factors associated with low back pain complaints in stone-cutting workers. This research was an analytic observation with a cross-sectional design. The research was conducted in Pero Village, Southwest Sumba District, in February-March 2020. The population consisted of 46 stone-cutting workers in Pero Village. The sample was taken using a total sampling technique. The statistical test used was the chi-square test with α=0.05. The results showed complaints of low back pain were related to work attitude (p=0.042), age (p=0.000), years of work (p=0.000), and length of work (p=0.031), while stretching did not associate with lower back pain (p=0.947). Stone cutting workers are recommended to have correct work posture (ergonomics) and to take time to rest, thereby minimizing the risk of LBP, especially for workers aged >30 years.